Political cartoons and the Israeli-Palestinian conflict - Danjoux, Ilan (New approaches to conflict analysis, 2012)
Examines Israeli and Palestinian editorial cartoons to explore whether changes in tone and content anticipated the outbreak of the Al-Aqsa Intifada in Oct. 2000.